P-645 Intra-ovarian injection of autologous platelet-rich plasma (PRP) in poor prognosis IVF patients within 1 year of treatment: a cohort study. (30th June 2022) - Barad, D; Albertini, D; Molinari, E; Gleicher, N
Abstract: Study question: Does intraovarian injection of platelet-rich plasma (PRP) change parameters of ovarian function in patients with evidence of diminished ovarian reserve? Summary answer: Over one year of follow-up there was no evidence of a positive effect of PRP treatment on ovarian function. What is known already: Several authors have previously reported positive outcomes and improved response in ovarian function after treatment with PRP. However, thus far, no randomized controlled trials and few cohort studies have been published. Study design, size, duration: This is a longitudinal cohort study following ovarian response among 80 patients with low functional ovarian reserve (LFOR) defined by AMH < 1.1 ng/mL, FSH > 12 mIU/mL or at least one prior IVF cycle with ≤ 3 oocytes for one year before and one year after intraovarian treatment with PRP. Participants/materials, setting, methods: 1.5 cc of PRP was injected into the cortex of ovaries in an average 12 injections per ovary. Beginning one month after their PRP treatment, patients underwent one or more cycles of ovulation induction for IVF. Outcome measures were endocrine response, and numbers of oocytes and embryos produced in by patients in response to a maximal gonadotropin stimulation before and after PRP treatment. Main results and the role of chance: In this study women between ages 28 and 54 failed to demonstrate statistically significant outcome benefits from intra-ovarian PRP. Two very poor-prognosis 40-year-old patients with prior failed IVF cycles at other IVF centers that never reached embryo transfer, however, achieved pregnancy in an IVF cycle following PRP treatment for an ongoing pregnancy rate of 4.7% if a patient following PRP achieved retrieval of at least 1 oocyte with IVF. Limitations, reasons for caution: This is an observational study of patients who performed poorly in past ovulation induction cycles, thus any improvement observed could have been accounted for by regression to the mean. The occurrence of two pregnancies in this group could be secondary to eventual success following a string of previous failures. Wider implications of the findings: Even extremely poor prognosis will occasionally achieve a successful outcome from IVF. Uncontrolled case series cannot provide sufficient evidence to support routine use of an intervention like PRP. Future studies demand the use of well- controlled randomized trials. Trial registration number: NCT04275700